Intraoperative Neurophysiological Monitoring of the Laryngeal Nerves During Anterior Neck Surgery: A Review. (January 2017) - Tewari, Anurag; Samy, Ravi N.; Castle, Joshua; Frye, Tiffany M.; Habeych, Miguel E.; Mohamed, Mahmoud
Contributions to the literature on intraoperative neuro monitoring (IONM) during endocrine and head and neck surgery have increased over recent years. Organizational support for neural monitoring during surgery is becoming evident and is increasingly recognized as an adjunct to visual nerve identification. A comprehensive understanding of the role of IONM for prevention of nerve injuries is critical to maximize safety during surgery of the anterior compartment of the neck. This review will explore the potential advantages of IONM to improve the outcomes among patients undergoing anterior neck surgery.